Kemudahan dan Kepercayaan Menggunakan E-Commerce Berpengaruh Terhadap Keputusan Dalam Pembelian Online dengan Metode Technology Acceptance Model - Dony Oscar; Endang Retnoningsih; Fandhilah Fandhilah (Universitas Bina Sarana Informatika, 2018)
Abstract - The use of e-commerce by consumers has provided many advantages that have been obtained both from the seller and even the buyer. The greater the interest of consumers in using ecommerce services is to make more and more players in providing e-commerce services and make them provide services to the best to the users. Basically, a site is information technology. Measuring the level of decisions in online purchases can use three variables such as ease of shopping, and trust in onile purchases will impact decisions on online purchases can be used in case studies of IT acceptance over the last few decades. In this study in 3 variables used using 116 samples with 9 questions and where all valid variables only 1 variable failed, with the value of reliability = 0.892> 0.6. Keyword: e-commerce, TAM, Decision